Functional impact of androgen‐targeted therapy on patients with castration‐resistant prostate cancer - Tomasz M. Beer; Neal Shore; Alicia Morgans; Kerri Winters‐Stone; Jeffrey S. Wefel; Daniel J. George (BJUI Compass, 2022)
Abstract Context Second‐generation androgen receptor inhibitors (ARIs) extend metastasis‐free survival, prolong overall survival, and delay symptoms when added to androgen deprivation therapy for the treatment of castration‐sensitive or castration‐resistant prostate cancer (CRPC). However, ARIs may adversely impact physical and cognitive function, thereby decreasing quality of life and prognosis. Objective To evaluate the evidence regarding the potential effects of ARIs on physical and cognitive function and to contextualize how drug‐related adverse effects may influence treatment decisions in CRPC. Evidence acquisition We performed a literature search using MEDLINE from January 1998 to June 2020 using terms relating to prostate cancer, androgen deprivation, and physical and cognitive function. We selected 61 publications for analysis. Evidence synthesis Treatment‐induced deterioration in physical and cognitive function may impair the independence and well‐being of patients with CRPC. Patient‐reported outcomes from clinical trials of ARIs provide quantitative evidence of their impact on these domains, which appears to vary between ARIs, reflecting the different adverse event profiles of these agents. Thus, the risk of physical or cognitive dysfunction may be managed or mitigated by appropriate selection of treatment options. Studies in patients with CRPC have assessed the cognitive effects of ARIs with validated instruments, whereas quantitative analysis of the impact on physical function has been limited. Conclusion Several validated instruments utilized for the assessment of physical and cognitive function in clinical studies have been adapted for clinical practice; however, consensus on the standardization of these assessments is required. Future clinical studies employing validated tools may generate data on the impact of ARIs and guide treatment decisions for patients with CRPC. Patient summary We review the hormonal therapies used to treat men with prostate cancer and the effects they have on physical and cognitive function. We discuss how to measure these effects and how this may assist when choosing treatment.